Experimental model of primary intraocular lymphoma based on BALB/CaNn strain and A20 cells is optimal for investigational research - Skrlova, Eva; Uherkova, Eva; Klimova, Aneta; Malarikova, Diana; Svozilkova, Petra; Matous, Petr; Herynek, Vit; Kucera, Tomas; Klener, Pavel; Heissigerova, Jarmila (Biomedical papers, 2025)
Aim. The purpose of this project was to compare the characteristics of two experimental murine models of primary intraocular lymphoma (PIOL) and determine which experimental model is most suitable for further investigational research to elucidate the pathophysiology of PIOL and to find new therapeutical strategies. Methods. In both experimental models PIOL was induced in immunocompetent mice with intravitreal injection of syngeneic B-cell lymphoma cell lines. Murine strain C3H/HeN and cell line 38C13 were used in the first model and BALB/CaNn mice and cell line A20 in the second model. During the experiments, thorough clinical evaluation (using photo documentation, ultrasonography, and MRI) and histological evaluation were performed. Results. In both models, the percentage of PIOL development was high, reaching nearly 80%. Disease progression was faster in C3H/HeN with exophthalmos occurring on average on day 10. Vitreous involvement was a predominant sign in the clinical presentation of this group. In BALB/CaNn mice exophthalmos occurred on average on day 22. The predominant clinical sign in the BALB/CaNn group was tumorous infiltration of the retina, optic disc, and tumorous retinal detachment. Conclusion. Slower progression of the disease in BALB/CaNn mice, greater possibility to examine the retina due to mild vitreous involvement, and later occurrence of exophthalmos makes this strain more suitable for further investigational research.
Keywords: primary intraocular lymphoma; murine experimental models; A20; 38C13